Optimization of Bacterial Cellulose Production from Wastewater of Noodle Processing by Komagataeibacter sp. PAP1 and Bio-Cellulose Paper Production - Tanyarat SUTTHIPHATKUL; Amornrat SUWANPOSRI; Duangjai OCHAIKUL (My University, 2020)
Bacterial Cellulose (BC) production from Fermented Rice Noodle Wastewater (FRNW) was fermented by Komagataeibacter sp. PAP1. In order to increase the production of BC, the FRNW-based medium was prepared and optimized for the cultivation of this bacterium. The optimized FRNW-based medium was composed of 5 % (w/v) mannitol, 0.1 % (w/v) beef extract, 0.5 % (v/v) ethanol, 1 % (v/v) acetic acid, pH 7.0 which were incubated at 30 °C for 10 days. Under these conditions, BC yielded 11.76 ± 0.34 g/L higher (4.40 fold) than the standard Hestrin-Schramm (HS) medium. The study on growth and BC production by Komagataeibacter sp. PAP1 in optimized culture condition showed that BC production by Komagataeibacter sp. PAP1 was growth-associated. The bacterial cell of Komagataeibacter sp. PAP1 increased exponentially from the 3rd to 5th day. The BC paper sheets produced using the obtained BC pellicle from an optimized FRNW-based medium gave higher mechanical strength than those from standard HS medium. This study reveals the use of FRNW as a substrate for BC production. The results indicated that FRNW, which is more environmentally friendly, can be used as an alternative low-cost substrate for BC production.
Keywords: Bacterial Cellulose; Advanced Cellulose Research Studies